2021
DOI: 10.3389/fonc.2021.644703
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of a Novel Deep Learning-Based Computed Tomography Perfusion Mapping Framework for Functional Lung Avoidance Radiotherapy

Abstract: Functional lung avoidance radiation therapy aims to minimize dose delivery to the normal lung tissue while favoring dose deposition in the defective lung tissue based on the regional function information. However, the clinical acquisition of pulmonary functional images is resource-demanding, inconvenient, and technically challenging. This study aims to investigate the deep learning-based lung functional image synthesis from the CT domain. Forty-two pulmonary macro-aggregated albumin SPECT/CT perfusion scans we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Ren et al implemented the DL-based approach to transform 3DCT to SPECT perfusion images and investigated the influence of different model architectures and preprocessing. 24,25 They reported that there were some cases in which the lowfunctional region was predicted to be a high-functional region, which can be partly attributed to the low occurrence and small volume of the low-functional regions compared with high-functional regions. Our results showed similar trends (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Ren et al implemented the DL-based approach to transform 3DCT to SPECT perfusion images and investigated the influence of different model architectures and preprocessing. 24,25 They reported that there were some cases in which the lowfunctional region was predicted to be a high-functional region, which can be partly attributed to the low occurrence and small volume of the low-functional regions compared with high-functional regions. Our results showed similar trends (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent layers combine these extracted features for advanced object detection. This property makes DL a suitable tool for image-related tasks, such as computer-aided diagnosis (27,28), image enhancement (29), image synthesis (30,31), and functional information derivation (32,33).…”
Section: DLmentioning
confidence: 99%
“…Like ventilation imaging, recent studies have also shown the use of CNN approaches to estimate lung perfusion from single energy CT scans. Ren et al 94 employed an attention U-net architecture to synthesize albumin SPECT/CT perfusion mapping from non-contrast CT scans to enable functional lung avoidance in radiotherapy planning. 94 Their proposed neural network is superior to the traditional U-Net architecture and is able to identify features from the CT domain that are compatible with perfusion defects with moderate correlation.…”
Section: Ai In Functional Assessmentmentioning
confidence: 99%
“…Ren et al 94 employed an attention U-net architecture to synthesize albumin SPECT/CT perfusion mapping from non-contrast CT scans to enable functional lung avoidance in radiotherapy planning. 94 Their proposed neural network is superior to the traditional U-Net architecture and is able to identify features from the CT domain that are compatible with perfusion defects with moderate correlation. Despite the limited size of the training (31 subjects) and testing data (11 subjects), these results illustrate the ability of deep learning approaches to estimate both ventilation and perfusion functional imaging from routine non-contrast CT scans under a common imaging platform.…”
Section: Ai In Functional Assessmentmentioning
confidence: 99%